Life-history and life-table parameters of fall armyworm (Spodoptera frugiperda) for maize (Zea mays) in tropical Indian condition - SOUJANYA, P LAKSHMI; SEKHAR, J C; SUBY, S B; KUMARI, A P PADMA; DIVYA, S; REDDY, M LAVA KUMAR; JAT, S L; RAKSHIT, SUJAY (The Indian Journal of Agricultural Sciences, 2022)
Fall armyworm (Spodoptera frugiperda (J. E. Smith)) is an invasive pest reported in 2018 from India which principally attacks maize during vegetative and reproductive stages. Investigations were carried out to understand biology of the pest in new tropical and sub-tropical environment for devising effective management strategies in maize. The biological aspects included morphometrics and life cycle of fall armyworm reared on maize under laboratory conditions at 26–31ºC and 50–65% relative humidity during August- September, 2018 to January-February, 2019 i.e. 34th to 6th standard weeks (SDW). Life table parameters including stage specific and age specific fecundity, population growth attributes and life expectancy of fall armyworm were computed. The diameter of eggs, length and width of body and their head capsules of different larval instars, pre-pupa, pupa, male and female adults were also measured.